Does studying abroad influence graduates’ wages? A literature review - Netz, Nicolai; Cordua, Fine (Journal of International Students, 2021)
In this article, we review quantitative studies that empirically examine whether studying abroad influences graduates’ wages. Our review suggests that studying abroad has a moderate positive effect on graduates’ early-career wages in various national and institutional settings. However, this effect tends to vary across groups of graduates, employment contexts, and types of stays abroad. Employer change, access to large and multinational companies, and access to high-wage labor markets abroad appear to be the most relevant mechanisms mediating the effect of studying abroad on wages. Other mechanisms, such as improved language skills and a greater tendency to pursue further education, turn out to be less relevant. Overall, our review illustrates that this area of research has made great progress in recent years, but it can be further advanced by standardization of study designs, internationally comparative and longitudinal datasets, analyses of further mediating mechanisms, and new research questions.